Precision Analysis of Poisson Control Chart Based on Sample Size - Elsa Resa Sari (Department of Mathematics, Hasanuddin University, 2020)
One technique used in performing statistical quality control is by poisson control chart. Poisson control chart used in data that have the same mean and varians for monitoring the number of defects in the study. In some cases, the different sample sizes influence the control chart performance. The control chart performance can be measured using average run length (ARL). The smaller ARL’s value, the better type of control chart. In this study, we used different sample sizes that is and mean . The result show the best performance of control chart is when and m = 200, because its has a smaller ARL’s value.